Stress test of the skin: The cutaneous permeability barrier treadmill - Schmuth, M. (Exp Dermatol, 2019)
Studying skin barrier function is central to our understanding of many skin disorders. The past decade has seen a surge of skin barrier related investigative work. Genetic, biochemical and cell biology experiments have added much evidence to the importance of the barrier in disease pathogenesis of a variety of disorders including ichthyosis, atopic dermatitis, and psoriasis. However, functional assays prove ever more important to demonstrate relevance of any of these findings. A paper published by Monash and Blank 60 years ago describes a stress test of the skin barrier, measuring skin barrier recovery, a functional test of tremendous implications as described in this editorial. This seminal paper has not been cited for almost 15 years, time to acknowledge its critical importance.